Pengaruh Kesesuaian Kompensasi, Pengendalian Internal, dan Good Corporate Governance Terhadap Pencegahan Kecurangan pada Koperasi (Studi Kasus Koperasi se-Kecamatan Buleleng): (Studi Kasus pada Koperasi Se-Kecamatan Buleleng) - Putu Indah Sonia Dewi; I Made Pradana Adiputra (Universitas Pendidikan Ganesha, 2022)
This study aimed to determine the influence of compensation suitability, internal control, and good corporate governance on the prevention of fraud in the case study of Cooperatives in Kecamatan Buleleng. This type of research is quantitative research. The population of this study were all active cooperatives in Kecamatan Buleleng, amounting to 134 cooperatives. The sample of this study was determined using the criteria and obtained a sample of 27 cooperatives. Then the data was processed using multiple linear regression analysis. The results of this study have portrayed: (1) The suitability of compensation positively affects on preventing fraud in Cooperatives in Kecamatan Buleleng, (2) Internal control positively affects on preventing fraud in Cooperatives in Kecamatan Buleleng, and (3) Good Corporate Governance positively affects on preventing fraud in Cooperatives in Kecamatan Buleleng.